Non-adherence to Treatment Among Iranian Dialysis Patients, A Systematic Review (Iranian Journal of Kidney Diseases, 2019)
Non-adherence to treatment is a common problem among hemodialysis (HD) patients and was considered as a reliable factor in patients deteriorating, increasing admission chance and inappropriate responding to HD treatment. According to multiple factors related to Non-adherence with HD treatment and its importance in patients’ quality of life, this study aims at a systematic reviewing of Non-adherence to treatment among Iranian dialysis patients. Treatment with adherence status is one of the problems that patients encounter during dialysis. This study aims at detecting the most important causes of Non-adherence in patients on dialysis according to previous studies. First, all of the studies related to our title were searched using main keywords (dialysis, hemodialysis, adherence, and non-adherence) for English and Persian databases; Iranmedex, Magi ran, SID, Iran doc, Google, Google scholar, PubMed, Embase, CINAHL, PsycInfo, and Cochrane Database of Systematic that covering the period from 2010 to 2018 was reviewing following a predefined inclusion and exclusion criteria. As a result, 40 papers related to inclusion and exclusion criteria were identified and analyzed. Data were collected according to study features, measures of Non-adherence, prevalence rates and factors related to Non-adherence. The PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines were followed to conduct this systematic review. According to the results of present study six main categories were found. The main reasons for Non-adherence with treatment in dialysis patients listed in the papers included: Patient related factors, socioeconomic factors, psychological factors, health care related factors, therapy related factors and disease-related factors.Trying to improve adherence is very important and can play a significant role in increaseing the health status among patients on dialysis.